Learn C programming - Szuhay, Jeff (Packt Publishing Ltd., 2022)
The foundation for many modern programming languages such as C++, C#, JavaScript, and Go, C is widely used as a system programming language as well as for embedded systems and high-performance computing. With this book, you'll be able to get up to speed with C in no time. The book takes you through basic programming concepts and shows you how to implement them in the C programming language. Throughout the book, you'll create and run programs that demonstrate essential C concepts, such as program structure with functions, control structures such as loops and conditional statements, and complex data structures. As you make progress, you'll get to grips with in-code documentation, testing, and validation methods. This new edition expands upon the use of enumerations, arrays, and additional C features, and provides two working programs based on the code used in the book. What's more, this book uses the method of intentional failure, where you'll develop a working program and then purposely break it to see what happens, thereby learning how to recognize possible mistakes when they happen. By the end of this C programming book, you'll have developed basic programming skills in C that can be easily applied to other programming languages and have gained a solid foundation for you to build on as a programmer.